Efficient versus flexible mentalizing in complex social settings: Exploring signature limits. (February 2016) - Schneider, Dana; Low, Jason
Abstract : Wu, Sheppard, and Mitchell ( Br. J. Psychol ., 2016; 107, 1–22) investigate in a fascinating study the fact that adults can detect empathic traits in others after only briefly watching or listening to a person. In this commentary, we highlight how the processes of an efficient, implicit, but inflexible mentalizing system are likely to operate in such situations. Further, we specify how testing signature limits over time‐, attribute‐, and protagonist‐restrictions can help distinguish whether an efficient‐implicit or flexible‐explicit mentalizing system is of relevance when processing complex social settings.